Soliton solutions to the (3+1)-dimensional KP and BA models using advanced exp⁡(-ϕ(ξ))-expansion scheme in mathematical physics - Zillu , Md. Mohiuddin; Ghosh, Supta; Biswas, Anita (International Journal of Physical Research, 2024)
In this manuscript, the main motivation is the implement of the advanced exp⁡(-ϕ(ξ)) -expansion method to construct the soliton solution, which contains some controlling parameters of two distinct equations via the Biswas-Arshed (BA) model and the (3+1)- dimensional Kadomtsev-Petviashvili (KP) equation. Here the behaviors of the solutions are presented in graphically under some condition on those parameters. The height of the wave, wave direction, and angle of the obtained wave are formed by substituting the particular values of the considerations over showing figures with control plot. With the collaboration of the advanced exp⁡(-ϕ(ξ))-expansion method, we construct entirely the solitary wave results as well as rogue type soliton, combined singular soliton, kink, singular kink, bright and dark soliton, periodic shape, double periodic shape soliton etc. Therefore, it is remarkable to perceive that the advanced exp⁡(-ϕ(ξ))-expansion method is easy, compatible and powerful mathematical tool to elucidation of exact results to other non-linear equivalences.